The Strategic Environmental Assessment in Decision Making about Transgenic Crops in Brazil - Pizella, Denise Gallo [UNESP]; Souza, Marcelo Pereira de (Univ Federal Parana, Editora, 2015)
The environmental use of transgenic crops is controversial, due to the uncertainties regarding the potential environmental, social and economic impacts that may arise. In order to regulate the decisions on the use of genetically modified organisms (GMOs), regulatory mechanisms that aim to predict such impacts were implemented in different countries, the risk analysis (RA) being the environmental study method normally used for making such decisions. However, there are objections as to its use as the unique tool for the environmental analysis of GMOs, since it does not allow the assessment of cumulative, indirect and long-term impacts and interests of countries as outlined on their policies, plans and programs (PPPs). One tool proposed by some authors likely to encompass such considerations is the Strategic Environmental Assessment (SEA), which seeks to consider the environmental variable during the planning stages. The purpose of this study was to identify the contribution of SEA to support decision-making processes involving the environmental use of transgenic crops in Brazil. Given that this activity is strategic for Brazilian agriculture, we analyzed it according to the parameters that determine good SEA practices. We found out that SEA can contribute to the taking of decisions regarding the commercial use of these cultivars, according to its principles of transparency, social Involvement, environmental planning, broad territorial scope, assessment of cumulative and long-term impacts and continuous environmental monitoring.
Keywords: GMO; biosafety; environmental planning